THE EFFECT OF DIGITAL COMPETENCE, EMPLOYEE INNOVATION, AND TECHNOLOGY SUPPORT ON EMPLOYEE PERFORMANCE AT THE DEPARTMENT OF CULTURE AND TOURISM TANJUNGPINANG CITY - Wahyurina; Sabri; Suyono (CV. Radja Publika, 2026)
This study aims to determine the influence of Digital Competence, Innovation and Technological Support on Performance atTanjungpinang City Culture and Tourism Office. The population in this study amounted to 80 respondents, using a saturated sampling technique so that the entire population became a sample, namely 80 respondents. The sampling technique was carried out with a saturated sample. Data collection was carried out by distributing questionnaires to respondents. The collected data were processed using SPSS software. The results of the study show that partially, Digital Competence has a significant effect on employee performance with a significance value of <0.001 (<0.05), Innovation has a significant effect on employee performance with a significance value of 0.002 (<0.05), and technological support has a significant effect on employee performance with a significance value of 0.004 (<0.05). Simultaneously, digital competence, innovation and technological support have a significant effect on employee performance with a significance value of 0.001 (<0.05).